Understanding the Pattern of International Migration: Challenges in Human Rights Protection - Bahri, Mohammad Thoriq (Jurnal Hukum, 2022)
International Migration can be described as the movement of people from one country to another county. The International Migration is one of the dynamic historical events, which was first legally regulated through the Tanzimat in the Ottoman Empire, signed on the 09 March 1857, which give the people who under the religious prosecuted legal permit to enter Turkey territory. Since then, the mass movement of the people between people becoming very common, especially after World War I, and World War II, when millions of people are moving from one region to another because of the displacement and violence. By utilizing Mixed Migration Center Dataset in 2019, which interviewed 9754 respondents, and the Mexican Government data on Migration in the year 2016, the main pattern of migration and motives are tracked and analyzed. It can be concluded, if the pattern of the migration is from East Africa to North Africa, East Africa to North Africa, East Africa to Southern Africa, East Africa to Europe, the Middle East to Europe, the Middle East to southeast Asia (Indonesia, Malaysia, and Thailand), Bangladesh/Myanmar to Malaysia, and from South America to North America. The motives are economics, Violence and General Security, and Lack of Rights. Still, International Migrants protection becoming a big challenge for many destination countries. From the analysis, can be concluded if the challenges in International Migrants Protection are because of the difference in terms, not all of the destination countries ratified the 1951 Convention about refugees and 1967 protocol as the legal basis and cultural and political context which make society in the destination countries refusing the International MigrantsInternational Migration can be described as the movement of people from one country to another county. The International Migration is one of the dynamic historical events, which was first legally regulated through the Tanzimat in the Ottoman Empire, signed on the 09 March 1857, which give the people who under the religious prosecuted legal permit to enter Turkey territory. Since then, the mass movement of the people between people becoming very common, especially after World War I, and World War II, when millions of people are moving from one region to another because of the displacement and violence. By utilizing Mixed Migration Center Dataset in 2019, which interviewed 9754 respondents, and the Mexican Government data on Migration in the year 2016, the main pattern of migration and motives are tracked and analyzed. It can be concluded, if the pattern of the migration is from East Africa to North Africa, East Africa to North Africa, East Africa to Southern Africa, East Africa to Europe, the Middle East to Europe, the Middle East to southeast Asia (Indonesia, Malaysia, and Thailand), Bangladesh/Myanmar to Malaysia, and from South America to North America. The motives are economics, Violence and General Security, and Lack of Rights. Still, International Migrants protection becoming a big challenge for many destination countries. From the analysis, can be concluded if the challenges in International Migrants Protection are because of the difference in terms, not all of the destination countries ratified the 1951 Convention about refugees and 1967 protocol as the legal basis and cultural and political context which make society in the destination countries refusing the International Migrants